Porcelain-like material and method for producing the same
Patent Information
- Application Number
- CN202611352838.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-02
- Publication Date
- 2026-10-16
AI Technical Summary
然而,现有密胺类仿瓷材料在实际应用中仍存在诸多不足
[0016] The porcelain-like material of this invention employs thermoplastic plastic material and porcelain-like filler material. The porcelain-like filler material in the gas contains a certain amount of cerium oxide, which can enhance the porcelain-like appearance of the material. Furthermore, the porcelain-like material of this invention also contains antibacterial agents, toughening agents, compatibilizers, lubricants, antioxidants, etc., thereby enabling the porcelain-like material to acquire the weight and texture of ceramics, while also possessing antibacterial properties. The porcelain-like material of this invention is prepared using a high-low temperature kneading and twin-screw compounding modification method, improving the dispersibility of the porcelain-like filler material and thermoplastic plastic material, and achieving excellent mechanical properties of the porcelain-like antibacterial composite material.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polymer composite materials and relates to a high-density, soft-touch porcelain-like material and its preparation method. Background Technology
[0002] Currently, melamine-based imitation porcelain materials on the market are a type of daily utensil with a ceramic appearance, made from thermosetting plastics formed by the condensation polymerization of melamine and formaldehyde as the base material and then molded. Compared with traditional ceramics, this type of material has advantages such as higher impact resistance, less breakage, brighter colors, and easier cleaning, while its production cost is much lower than that of ceramics. Therefore, it is widely used in the catering industry and home settings. However, existing melamine-based imitation porcelain materials still have many shortcomings in practical applications.
[0003] Melamine resin is prone to decomposition and release of melamine monomers under high temperature or acidic environments. After prolonged use, fine cracks may appear on the surface, affecting the appearance and lifespan of the product. The density of melamine resin is approximately 1.5-1.8 g / cm³. 3 It is significantly lower than the 2.5 g / cm³ of ceramics. 3 This results in products that feel light and lack the weight and texture of ceramics, and their surface antibacterial function is difficult to maintain for long. To increase the density of imitation porcelain materials to approximate the feel of ceramics, current technologies often add high amounts of mineral powders such as calcium carbonate or barium sulfate. However, high filler content leads to a sharp decline in the material's mechanical properties, especially impact strength and toughness, increasing the brittleness of the product. High-content mineral powders and resin matrices are prone to uneven dispersion and localized density differences during twin-screw extrusion granulation, affecting the stability of product quality. Furthermore, conventional inorganic or organic antibacterial agents in highly filled mineral systems suffer from significantly reduced antibacterial effects due to the adsorption or coating of active components by a large amount of filler, making it difficult to meet hygiene and safety requirements.
[0004] It is evident that existing melamine-based imitation porcelain materials, while maintaining the appearance of ceramics, cannot simultaneously achieve a synergistic improvement in density, feel, mechanical properties, durability, and antibacterial function. Therefore, there is an urgent need to develop a new type of imitation porcelain material and its preparation method to effectively improve the porcelain-like feel of the imitation porcelain material, that is, to achieve a density, feel, and gloss close to that of ceramics, while maintaining good mechanical properties and long-lasting antibacterial effects. Summary of the Invention
[0005] To address the aforementioned shortcomings, this invention provides a porcelain-like material and its preparation method.
[0006] The first aspect of the present invention provides a porcelain-like material, comprising a thermoplastic plastic material and a porcelain-like filler material, wherein the porcelain-like filler material comprises cerium clay powder, and the cerium clay powder accounts for 10-30% of the mass of the porcelain-like filler material.
[0007] According to one embodiment of the present invention, based on 100 parts by weight of the total weight of the imitation porcelain material, the imitation porcelain material comprises 19-45 parts by weight of the thermoplastic plastic material, 50-70 parts by weight of the imitation porcelain filler material, 4-10 parts by weight of the toughening agent and 3-8 parts by weight of other additives.
[0008] According to another embodiment of the present invention, the imitation porcelain filler material further includes zirconium dioxide powder, titanium dioxide and silicate powder; the zirconium dioxide powder accounts for 60-80% of the mass of the imitation porcelain filler material; the titanium dioxide accounts for 5-15% of the mass of the imitation porcelain filler material; and the silicate powder accounts for 5-10% of the mass of the imitation porcelain filler material.
[0009] According to another embodiment of the present invention, the density of the porcelain-like filler material is ≥5.8 g / cm³. 3 , whiteness ≥97%, mesh size 1000-2000 mesh.
[0010] According to another embodiment of the present invention, the zirconium dioxide powder has a mesh size of 2000-3000 mesh and a whiteness ≥98%; the titanium dioxide is rutile type, with a mesh size of 1000-2000 mesh and a whiteness ≥99%; the cerium oxide powder has a mesh size of 1000-2000 mesh; and the silicate powder has a mesh size of 1000-2000 mesh.
[0011] According to another embodiment of the present invention, the thermoplastic material is polypropylene, polybutylene terephthalate, or polycarbonate. Preferably, the polypropylene content is 19-31 parts by weight. Preferably, the polypropylene material is an impact copolymer polypropylene material with a vinyl content of about 8-10% and a melt index of 20-30 g / 10 min. Preferably, the polybutylene terephthalate content is 25-36 parts by weight. Preferably, the polybutylene terephthalate has a number-average molecular weight of 20,000-30,000 and a melt index of 15-25 g / 10 min. Preferably, the polycarbonate content is 30-45 parts by weight, more preferably 35-40 parts by weight. Preferably, the polycarbonate has a number-average molecular weight of 18,000-22,000 and a melt index of 15-25 g / 10 min.
[0012] According to another embodiment of the present invention, the toughening agent is one or more of the following: a terpolymer of ethylene, propylene and non-conjugated diene monomers; an ethylene-butene copolymer; an ethylene-octene copolymer; an ethylene-propylene and α-olefin copolymer; a hydrogenated styrene-butadiene block copolymer; a styrene-butadiene-styrene block copolymer or a derivative thereof; and an ethylene-butyl acrylate copolymer or a derivative thereof.
[0013] According to another embodiment of the present invention, the other additives include one or more of antibacterial agents, compatibilizers, lubricants, and antioxidants. Preferably, the antibacterial agent is an inorganic transparent zinc-based antibacterial agent, and its addition amount is 0.8-1.2% of the total weight of the imitation porcelain material. Preferably, the compatibilizer is a complex of a coupling agent and a compatibilizer, wherein the coupling agent is one or more of silane, titanate, and aluminate coupling agents, and the compatibilizer is one or more of ABS-g-MAH, PE-g-MAH, PP-g-MAH, and POE-g-MAH. More preferably, the addition amount of the coupling agent is 0.6-1.0% of the total weight of the imitation porcelain material, and the addition amount of the compatibilizer is 2-5% of the total weight of the imitation porcelain material. Preferably, the lubricant is one or more of polyethylene wax, polypropylene wax, zinc stearate, and N,N-ethylene bis-stearamide. Preferably, the antioxidant is one or more of 1076, 168, 1010, and CA.
[0014] A second aspect of the present invention provides a method for preparing the above-mentioned imitation porcelain material, comprising: adding 10-15 parts by weight of the thermoplastic plastic material to a high-temperature mixer, setting the mixer temperature to 90-120°C, and stirring for 3-5 minutes; then adding the porcelain filler, the coupling agent, the antioxidant, and the lubricant to the high-temperature mixer according to the weight ratio, and continuing to stir at high speed for 10-15 minutes to obtain a first premix; placing the first premix in a low-temperature mixer to pulverize and disperse, and cooling to room temperature to obtain a second premix; placing the second premix, the remaining thermoplastic plastic material, and the compatibilizer in a mixer to mix for 5-10 minutes, and then adding it to a parallel twin-screw extruder for extrusion granulation.
[0015] According to one embodiment of the present invention, the twin-screw extruder has a screw diameter of Φ≥45mm, a screw compression ratio of 2.5-3.5, and a screw length-to-diameter ratio of ≥40:1.
[0016] The porcelain-like material of this invention employs thermoplastic plastic material and porcelain-like filler material. The porcelain-like filler material in the gas contains a certain amount of cerium oxide, which can enhance the porcelain-like appearance of the material. Furthermore, the porcelain-like material of this invention also contains antibacterial agents, toughening agents, compatibilizers, lubricants, antioxidants, etc., thereby enabling the porcelain-like material to acquire the weight and texture of ceramics, while also possessing antibacterial properties. The porcelain-like material of this invention is prepared using a high-low temperature kneading and twin-screw compounding modification method, improving the dispersibility of the porcelain-like filler material and thermoplastic plastic material, and achieving excellent mechanical properties of the porcelain-like antibacterial composite material. Detailed Implementation
[0017] To make the present invention clearer and easier to understand, the technical solution of the present invention will be further described below with reference to specific embodiments. The embodiments described below are only used to explain the present invention and are not intended to limit the present invention in any form or substance.
[0018] The porcelain-like material of the present invention includes a thermoplastic plastic material and a porcelain-like filler material. The porcelain-like filler material includes cerium clay powder, which accounts for 10-30% of the mass of the porcelain-like filler material. By adding a certain amount of cerium clay powder, the porcelain-like appearance of the porcelain-like material of the present invention can be improved.
[0019] In an optional embodiment, based on 100 parts by weight of the total weight of the imitation porcelain material, the imitation porcelain material comprises 19-45 parts by weight of thermoplastic plastic material, 50-70 parts by weight of imitation porcelain filler material, 4-10 parts by weight of toughening agent and 3-8 parts by weight of other additives.
[0020] In an optional embodiment, the porcelain-like filler material further includes zirconium dioxide powder, titanium dioxide, and silicate powder. The zirconium dioxide powder accounts for 60-80% of the mass of the porcelain-like filler material. The titanium dioxide accounts for 5-15% of the mass of the porcelain-like filler material. The silicate powder accounts for 5-10% of the mass of the porcelain-like filler material.
[0021] In an optional embodiment, the density of the porcelain-like filler material is ≥5.8 g / cm³. 3 , whiteness ≥97%, mesh size 1000-2000 mesh.
[0022] In optional embodiments, the zirconium dioxide powder has a mesh size of 2000-3000 mesh and a whiteness ≥98%. The titanium dioxide is rutile type, with a mesh size of 1000-2000 mesh and a whiteness ≥99%. The cerium oxide powder has a mesh size of 1000-2000 mesh. The silicate powder has a mesh size of 1000-2000 mesh.
[0023] In an optional embodiment, the thermoplastic material is polypropylene, polybutylene terephthalate, or polycarbonate.
[0024] The polypropylene content in imitation porcelain materials can be 19-31 parts by weight. The polypropylene material can be impact copolymer polypropylene, with a vinyl content of about 8-10% and a melt flow index of 20-30 g / 10min.
[0025] The content of polybutylene terephthalate in the imitation porcelain material can be 25-36 parts by weight. The number average molecular weight of polybutylene terephthalate is 20,000-30,000, and the melt index is 15-25 g / 10 min.
[0026] The polycarbonate content in the imitation porcelain material is 25-45 parts by weight, preferably 35-40 parts by weight. If the polycarbonate content in the imitation porcelain material is less than 25 parts, the mechanical properties of the material decrease significantly; if the content is higher than 45 parts, the density improvement of the imitation porcelain material is limited. Preferably, the number-average molecular weight of the polycarbonate is 18,000-22,000, and the melt index is 15-25 g / 10 min. The melt index of polycarbonate affects the processing performance of the material. Low melt index polycarbonate materials have poor processing performance and are not conducive to injection molding, while high melt index polycarbonate materials show a significant decrease in impact and tensile properties.
[0027] In optional embodiments, the toughening agent is one or more of the following: terpolymers of ethylene, propylene and non-conjugated dienes as monomers; ethylene-butene copolymers; ethylene-octene copolymers; ethylene-propylene and α-olefin copolymers; hydrogenated styrene-butadiene block copolymers; styrene-butadiene-styrene block copolymers or their derivatives; ethylene-methyl acrylate copolymers or their derivatives; and ethylene-butyl acrylate copolymers or their derivatives.
[0028] Toughening agents can be used in combination with specific thermoplastic materials to achieve better mechanical properties. For example, when the thermoplastic material is polypropylene, the toughening agent can be one or more of the following: terpolymers of ethylene-propylene and non-conjugated dienes, styrene-butadiene-styrene block copolymers, or their derivatives, to improve the impact resistance of high-density porcelain-like antibacterial polypropylene materials. POE plastics are thermoplastic elastomers polymerized in situ using metallocene catalysts to polymerize ethylene and octene. They possess excellent toughness, good processability, excellent aging resistance, and good compatibility with polypropylene. Good flowability also improves filler dispersion and increases weld line strength. Terpolymers of ethylene-propylene and non-conjugated dienes exhibit excellent aging resistance, corrosion resistance, excellent elasticity, and low surface self-adhesion. They also have excellent filling capacity with minimal reduction in physical and mechanical properties. Styrene-butadiene-styrene block copolymers possess excellent tensile strength, elasticity, and electrical properties, with low permanent deformation, good flexural and resilience, and high surface friction. Ethylene-propylene and α-olefin copolymers (POP materials) have excellent toughness, excellent impact strength and excellent low-temperature performance. At the same time, POP has good processing properties. It is sensitive to shear rate, and its viscosity decreases rapidly at high shear rates, making it easy to process.
[0029] When the thermoplastic material is polybutylene terephthalate, the toughening agent can be hydrogenated styrene-butadiene block copolymer (SEBS material), which gives the imitation porcelain material excellent toughness, excellent impact strength and excellent low temperature performance.
[0030] When the thermoplastic material is polycarbonate, toughening agents such as ethylene-methyl acrylate copolymer, ethylene-butyl acrylate copolymer, or their derivatives can be used to improve the impact resistance of the imitation porcelain material. Ethylene-methyl acrylate copolymer is a high-pressure α-olefin random copolymer formed by polymerizing ethylene and methyl acrylate in a high-pressure reactor. The methyl acrylate content is 18%-24%, and the melt index is 0.5-20 g / 10 min. It possesses excellent thermal stability, compatibility, and high filler carrying capacity. Blending with polycarbonate can improve impact strength and toughness, enhance hot-melt bonding performance, improve adhesion, and reduce stiffness.
[0031] The above combinations are just examples; of course, there can be other combinations as well.
[0032] In optional embodiments, other additives include one or more of antibacterial agents, compatibilizers, lubricants, and antioxidants. Preferably, the antibacterial agent is an inorganic transparent zinc-based antibacterial agent, and its addition amount is 0.8-1.2% of the total weight of the imitation porcelain material. The compatibilizer is a complex of a coupling agent and a compatibilizer. The coupling agent is one or more of silane, titanate, and aluminate coupling agents, and the compatibilizer is one or more of ABS-g-MAH, PE-g-MAH, PP-g-MAH, and POE-g-MAH. The addition amount of the coupling agent is 0.6-1.0% of the total weight of the imitation porcelain material, and the addition amount of the compatibilizer is 2-5% of the total weight of the imitation porcelain material. The lubricant is one or more of polyethylene wax, polypropylene wax, zinc stearate, and N,N-ethylene bis-stearamide. The antioxidant is one or more of 1076, 168, 1010, and CA.
[0033] The second aspect of the present invention provides a method for preparing the above-mentioned imitation porcelain material, comprising: adding 10-15 parts by weight of thermoplastic plastic material to a high-temperature mixer, setting the mixer temperature to 90-120°C, and stirring for 3-5 minutes; then adding ceramic filler, coupling agent, antioxidant, and lubricant to the high-temperature mixer according to the weight ratio, and continuing to stir at high speed for 10-15 minutes to obtain a first premix; placing the first premix in a low-temperature mixer to pulverize and disperse, and cooling to room temperature to obtain a second premix; placing the second premix, the remaining thermoplastic plastic material, and the compatibilizer in a mixer to mix for 5-10 minutes, and then adding it to a parallel twin-screw extruder for extrusion granulation.
[0034] According to one embodiment of the present invention, the screw of the twin-screw extruder has a screw diameter of ≥45mm, a screw compression ratio of 2.5-3.5, and a screw length-to-diameter ratio of ≥40:1.
[0035] The present invention is further described below through specific examples. However, these examples are merely exemplary and do not constitute any limitation on the scope of protection of the present invention. Unless otherwise specified, the reagents, materials, and instruments used in the following embodiments are commercially available.
[0036] The physical properties of the following embodiments and comparative examples were evaluated according to the following test methods: Density: evaluated based on GB / T 1033.2-2010; Melt Flow Index (MFR): Evaluated based on GB / T 3682.1-2018; Tensile strength: evaluated based on GB / T 1040.2-2006; Bending strength: evaluated based on GB / T 9341-2008; Impact strength of cantilever beam: evaluated based on GB / T 1843-2008; The specific implementation method is as follows: As required, the following raw material types were used in the embodiments and comparative examples, as shown in Table 1.
[0037] Table 1
[0038] The specific preparation method is as follows: S1, weigh out polycarbonate resin, toughening agent, imitation porcelain material, inorganic mineral powder, coupling agent, antioxidant, lubricant and other additives according to the weight ratio; S2, preheat the high-speed mixer, set the temperature to 60℃, first add polycarbonate resin and toughening agent, stir evenly, then add imitation porcelain material, inorganic mineral powder and coupling agent, stir for 10 minutes, then add antioxidant, lubricant and other additives, continue stirring for 5 minutes, then release and cool for later use. S3 feeds the mixed material into a high-torque twin-screw extruder, where it is sheared and mixed by the screws before being extruded. The material is then water-cooled, stretched, air-dried, pelletized, and dried to produce a high-density imitation porcelain polycarbonate material.
[0039] Implementation Cases 1-4: Polypropylene Porcelain-like Antibacterial Composite Material
[0040] The thermoplastic material in Examples 1-4 is polypropylene.
[0041] The imitation porcelain filler material is a composite of various mineral powders, including zirconium dioxide, titanium dioxide, cerium oxide, and silicates. The zirconium dioxide has the following characteristics: a mesh size of 2000 and a density of 5.85 g / cm³. 3 The whiteness is 98.5%; the characteristic parameters of titanium dioxide are a mesh size of 1250 mesh and a density of 4.26 g / cm³. 3The whiteness is 99.5%; the characteristic parameters of cerium clay are a mesh size of 1000 mesh and a density of 7.3 g / cm³. 3 The whiteness is approximately 96%; the silicate is mainly composed of kaolin and feldspar, with a mesh size of 1000 mesh and a density of 2.5 g / cm³. 3 The whiteness is approximately 96%.
[0042] Table 2 shows a comparison of the different compositions and properties of the imitation porcelain filler materials used in each embodiment.
[0043] Table 2
[0044] The antibacterial agent is an inorganic transparent zinc-based antibacterial agent, a white powder, with a temperature resistance of ≥300℃ and a whiteness of ≥95%.
[0045] The toughening agent is an ethylene-propylene-α-olefin copolymer (POP material).
[0046] The compatibilizer is a combination of coupling agent and compatibilizer. The coupling agent is an aluminum-titanium composite agent with a thermal decomposition temperature >280℃; the compatibilizer is PP-g-MAH with a grafting rate >0.8%.
[0047] The lubricant is N,N-ethylene bis-stearamide, with a thermal decomposition temperature >280℃ and a particle size of about 10-30μm.
[0048] The antioxidants are a combination of 168 and 1010.
[0049] The imitation porcelain materials of Examples 1-4 were prepared by different ratios, and the composition and performance results of each group of samples are listed in Table 3.
[0050] Table 3
[0051] In Table 3, the other additives in Examples 1 and 2 include 0.7% coupling agent, 0.3% antioxidant, 1% antibacterial agent, 1.5% lubricant, and 1.5% compatibilizer; the other additives in Examples 3 and 4 include 0.7% coupling agent, 0.3% antioxidant, 1% antibacterial agent, 1.5% lubricant, and 2.5% compatibilizer.
[0052] The imitation porcelain materials prepared in Examples 1-4 were tested and found to have an antibacterial effect of up to 98% (Escherichia coli, Staphylococcus aureus, and Candida albicans). At the same time, the materials have excellent imitation porcelain feel and excellent mechanical properties, and also have excellent processability. They can be processed by thermoplastic materials such as injection molding, casting, and compression molding, and can be used for daily necessities, stationery, and small office supplies.
[0053] Implementation Case 5-8: Polybutylene terephthalate (PBT) Porcelain-like Antibacterial Composite Material
[0054] The thermoplastic material in Examples 5-8 is polybutylene terephthalate.
[0055] The porcelain-like filler material is prepared from a composite of various mineral powders, including zirconium dioxide, titanium dioxide, cerium clay, and silicates. The zirconium dioxide has the following characteristics: a mesh size of 2000 and a density of 5.85 g / cm³. 3 The whiteness is 98.5%; the characteristic parameters of titanium dioxide are a mesh size of 1250 mesh and a density of 4.26 g / cm³. 3 The whiteness is 99.5%; the characteristic parameters of cerium clay are a mesh size of 1000 mesh and a density of 7.3 g / cm³. 3 The whiteness is approximately 96%; the silicate is mainly composed of kaolin and feldspar, with a mesh size of 1000 mesh and a relative density of 2.5 g / cm³. 3 The whiteness is approximately 96%.
[0056] Table 4 shows a comparison of the different compositions and properties of the imitation porcelain filler materials used in each embodiment.
[0057] Table 4
[0058] The antibacterial agent is an inorganic transparent zinc-based antibacterial agent, a white powder, with a temperature resistance of ≥300℃ and a whiteness of ≥95%.
[0059] The toughening agent is hydrogenated styrene-butadiene block copolymer (SEBS material).
[0060] The compatibilizer is a combination of coupling agent and compatibilizer. The coupling agent is an aluminum-titanium composite agent with a thermal decomposition temperature >280℃; the compatibilizer is SEBS-g-MAH with a grafting rate >0.8%.
[0061] The lubricant is polyethylene wax with a softening point of about 100°C and a purity of >98%.
[0062] The antioxidants are a combination of 168 and 1010.
[0063] The imitation porcelain materials of Examples 5-8 were prepared using different ratios, and the composition and performance results of each group of samples are listed in Table 5.
[0064] Table 5
[0065] In Table 5, the other additives in Examples 5 and 6 include 0.7% coupling agent, 0.3% antioxidant, 1% antibacterial agent, 1.5% lubricant, and 1.5% compatibilizer; in Examples 7 and 8, the other additives include 0.7% coupling agent, 0.3% antioxidant, 1% antibacterial agent, 1.5% lubricant, and 2.5% compatibilizer.
[0066] The imitation porcelain materials prepared in Examples 5-8 were tested and found to have an antibacterial effect of up to 98% (Escherichia coli, Staphylococcus aureus, and Candida albicans). At the same time, the materials have excellent imitation porcelain feel and excellent mechanical properties, and have excellent processability. They can be processed by thermoplastic materials such as injection molding, casting, and compression molding, and can be used for daily necessities, stationery, and small office supplies.
[0067] Examples 9-12: Carbonate-based antibacterial composite materials with a porcelain-like feel
[0068] The thermoplastic material in Examples 9-12 is polycarbonate.
[0069] The porcelain-like filler material is prepared from a composite of various mineral powders, including zirconium dioxide, titanium dioxide, cerium oxide, and silicates. The zirconium dioxide has the following characteristics: a mesh size of 2000 and a relative density of 5.85 g / cm³. 3 The whiteness is 98.5%. The characteristic parameters of titanium dioxide are: mesh size 1250, relative density 4.26 g / cm³. 3 The whiteness is 99.5%. The characteristic parameters of cerium clay are: mesh size 1000, relative density 7.3 g / cm³. 3 The whiteness is approximately 96%. The silicate is mainly composed of kaolin and feldspar, with a mesh size of 1000 and a relative density of 2.5 g / cm³. 3 The whiteness is approximately 96%.
[0070] Table 6 shows a comparison of the different compositions and properties of the imitation porcelain filler materials used in each embodiment.
[0071] Table 6
[0072] The antibacterial agent is an inorganic transparent zinc-based antibacterial agent, a white powder, with a temperature resistance of ≥300℃ and a whiteness of ≥95%.
[0073] The toughening agent is Arkema / 28MA07 from France.
[0074] The compatibilizer is a combination of coupling agent and compatibilizer. The coupling agent is an aluminate; the compatibilizer is ABS-g-MAH, with a grafting rate >0.8%.
[0075] The lubricant is polyethylene wax.
[0076] The antioxidant is antioxidant 1076.
[0077] The imitation porcelain materials of Examples 9-12 were prepared using different ratios, and the composition and performance results of each group of samples are listed in Table 7.
[0078] Table 7
[0079] In Table 7, the other additives in Examples 9-10 include 0.7% coupling agent, 0.3% antioxidant, 1% antibacterial agent, 1.5% lubricant, and 1.5% compatibilizer; the imitation porcelain materials prepared in Examples 9-12 of Examples 11-12 can be used in injection molded products such as stationery (ballpoint pen accessories, fountain pen shells, pen holders, etc.), office supplies (file baskets, stapler shells, calculator shells, etc.), daily necessities (folder covers, etc.), and storage products (pen holders, etc.).
[0080] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.
Claims
1. A porcelain-like material, characterized in that, It includes thermoplastic plastic materials and imitation porcelain filler materials, wherein the imitation porcelain filler materials include cerium clay powder, and the cerium clay powder accounts for 10-30% of the mass of the imitation porcelain filler materials.
2. The imitation porcelain material according to claim 1, characterized in that, Based on 100 parts by weight of the total weight of the imitation porcelain material, the imitation porcelain material comprises 19-45 parts by weight of the thermoplastic plastic material, 50-70 parts by weight of the imitation porcelain filler material, 4-10 parts by weight of the toughening agent and 3-8 parts by weight of other additives.
3. The imitation porcelain material according to claim 1, characterized in that, The porcelain-like filler material further includes zirconium dioxide powder, titanium dioxide, and silicate powder; the zirconium dioxide powder accounts for 60-80% of the mass of the porcelain-like filler material; the titanium dioxide accounts for 5-15% of the mass of the porcelain-like filler material; the silicate powder accounts for 5-10% of the mass of the porcelain-like filler material; and / or The density of the imitation porcelain filler material is ≥5.8 g / cm³. 3 , whiteness ≥97%, mesh size 1000-2000 mesh.
4. The imitation porcelain material according to claim 3, characterized in that, The zirconium dioxide powder has a mesh size of 2000-3000 and a whiteness of ≥98%; the titanium dioxide is rutile type, with a mesh size of 1000-2000 and a whiteness of ≥99%; the cerium oxide powder has a mesh size of 1000-2000; and the silicate powder has a mesh size of 1000-2000.
5. The imitation porcelain material according to any one of claims 2-4, characterized in that, The thermoplastic material is polypropylene, polybutylene terephthalate, or polycarbonate. Preferably, the polypropylene material content is 19-31 parts by weight; Preferably, the polypropylene material is an impact-resistant copolymer polypropylene material with a vinyl content of about 8-10% and a melt flow index of 20-30 g / 10 min; Preferably, the content of polybutylene terephthalate is 25-36 parts by weight; Preferably, the polybutylene terephthalate has a number-average molecular weight of 20,000-30,000 and a melt index of 15-25 g / 10 min; Preferably, the polycarbonate content is 30-45 parts by weight, more preferably 35-40 parts by weight; Preferably, the polycarbonate has a number-average molecular weight of 18,000-22,000 and a melt index of 15-25 g / 10 min.
6. The imitation porcelain material according to any one of claims 2-5, characterized in that, The toughening agent is one or more of the following: terpolymers with ethylene, propylene and non-conjugated dienes as monomers; ethylene-butene copolymers; ethylene-octene copolymers; ethylene-propylene and α-olefin copolymers; hydrogenated styrene-butadiene block copolymers; styrene-butadiene-styrene block copolymers or their derivatives; and ethylene-butyl acrylate copolymers or their derivatives.
7. The imitation porcelain material according to any one of claims 2-6, characterized in that, The other additives include one or more of the following: antibacterial agents, compatibilizers, lubricants, and antioxidants; Preferably, the antibacterial agent is an inorganic transparent zinc-based antibacterial agent, and its addition amount is 0.8-1.2% of the total weight of the imitation porcelain material; Preferably, the compatibilizer is a complex of a coupling agent and a compatibilizer, wherein the coupling agent is one or more selected from silanes, titanates, and aluminates, and the compatibilizer is one or more selected from ABS-g-MAH, PE-g-MAH, PP-g-MAH, and POE-g-MAH; more preferably, the amount of the coupling agent added is 0.6-1.0% of the total weight of the imitation porcelain material, and the amount of the compatibilizer added is 2-5% of the total weight of the imitation porcelain material. Preferably, the lubricant is one or more of polyethylene wax, polypropylene wax, zinc stearate, and N,N-ethylene bis-stearamide; Preferably, the antioxidant is one or more of 1076, 168, 1010, and CA.
8. A method for preparing a porcelain-like material according to any one of claims 1-7, characterized in that, include: Add 10-15 parts by weight of the thermoplastic material to a high-temperature mixer, set the mixer temperature to 90-120°C, and stir for 3-5 minutes. Then, according to the weight ratio, the ceramic filler material, the coupling agent, the antioxidant, and the lubricant are added to the high-temperature mixer, and the mixture is stirred at high speed for 10-15 minutes to obtain the first premix. The first premix was placed in a low-temperature mixer to be pulverized and dispersed, and then cooled to room temperature to obtain the second premix. The second premix, the remaining thermoplastic material, and the compatibilizer are placed in a mixer and mixed for 5-10 minutes, then added to a parallel twin-screw extruder for extrusion granulation.
9. The preparation method according to claim 8, characterized in that, The twin-screw extruder has a screw diameter of ≥45mm, a screw compression ratio of 2.5-3.5, and a screw length-to-diameter ratio of ≥40:1.